Effect of Dhee-Dhriti-Smriti Model in Smartphone Addiction - Ankita Kishor Kale; H. P. Savitha; M. Vinay Shankar; S. Y. Thanushree Yogee (Journal of Ayurveda)
Introduction:The usage of smartphones has permeated every aspect of daily life. Particularly, young individuals are frequently seen using their smartphones to make or receive calls, as well as to utilize various applications or just tap on touch displays for extended periods. The options afforded by smartphones are tempting, and the total duration of using smartphones each day is extremely high for many individuals. The psychospiritual method of Satvavajaya Chikitsa, an Ayurveda psychotherapy, is specifically targeted at the mind and its associated qualities. Our goal in this study was to define, examine, and manage a potential instance of smartphone addiction using the Dhee-Dhriti-Smriti model. Main Clinical Findings:A 14-year male child had a complaint of an increased use of mobile phone for the past 1 year, which initially started in the lockdown due to online classes, associated with anger outbursts and irritation. Diagnosis:The patient was diagnosed with Substance abuse disorder. Intervention:The patient was treated with Ayurvedic psychotherapy Satvavajaya Chikitsa and Ayurvedic internal medications Manasamitra Vati and Saraswatarishta. Outcomes:There was a significant reduction in the usage of smartphone from an average of 6–7 h to half an hour. Conclusion:This case study demonstrates the potential and usefulness of Satvavajaya Chikitsa in the management of smartphone addiction.